2012
DOI: 10.26719/2012.18.4.318
|View full text |Cite
|
Sign up to set email alerts
|

318 Verbal and physical abuse against Jordanian nurses in the work environment

Abstract: This descriptive cross-sectional study determined the prevalence and sources of verbal and physical workplace abuse in the last 6 months, the nurses' reactions to abuse, and their opinions about it. Data were collected by questionnaire from 447 nurses working in various departments in 3 hospitals in Amman. The prevalence of verbal and physical abuse was 37.1% and 18.3% respectively. Younger, less experienced nurses and those in emergency and intensive care departments experienced more abuse. Patients and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
101
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 16 publications
23
101
4
6
Order By: Relevance
“…In the literature, frequencies varying between 2% and 75% for physical violence, 37% and 100% for verbal violence, and 3% and 30% for mobbing were reported, figures that varied depending on the actual differences as well as the differences in methodology (4-6,9,11,13,14, [16][17][18][19][20][21][22]. In studies reporting lower percentages of physical and verbal violence in comparison to our study, different health personnel were evaluated together, and studies identifying a lower frequency of mobbing than our study were conducted among nurses from psychiatric wards (9,13,16,18,20). Many studies frequently report that nurses working in psychiatric wards are most subject to physical and verbal violence (4,9,14,17,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, frequencies varying between 2% and 75% for physical violence, 37% and 100% for verbal violence, and 3% and 30% for mobbing were reported, figures that varied depending on the actual differences as well as the differences in methodology (4-6,9,11,13,14, [16][17][18][19][20][21][22]. In studies reporting lower percentages of physical and verbal violence in comparison to our study, different health personnel were evaluated together, and studies identifying a lower frequency of mobbing than our study were conducted among nurses from psychiatric wards (9,13,16,18,20). Many studies frequently report that nurses working in psychiatric wards are most subject to physical and verbal violence (4,9,14,17,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that staff nurses had experienced more violence than ANMs which is paradoxical with the findings of a study conducted in Iran and Jordan, which showed that nurses with lower position were exposed to workplace violence. 7,23 The difference in findings might be due to variation in age and working experience between nurses and ANMs. Unlike with this study results, a study conducted in Southern Thailand 19 showed that nurses working in rotating shifts experienced more violence than nurses in fixed shifts.…”
Section: Resultsmentioning
confidence: 99%
“…Perpetrators may be co-workers, managers, patients or visitors (3). The majority of acts of physical or verbal aggression originate from patients or visitors (4)(5)(6)(7)(8)(9). While most incidents of patient or visitor aggression (PVA) arise in mental health and accident and emergency departments (10,11), PVA also occurs in other clinical settings, such as medical and surgical departments (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…While most incidents of patient or visitor aggression (PVA) arise in mental health and accident and emergency departments (10,11), PVA also occurs in other clinical settings, such as medical and surgical departments (12,13). Frequent staff exposure to aggression hampers recruitment and retention, and engenders a multitude of problems in the workforce, such as heightened risk of burnout, sleep disturbance, anxiety, as well as intent to leave the profession (6,9,14,15). PVA is influenced by a variety of internal, external and interactional factors (16) and there is to date no comprehensive theory of PVA and how it emerges in the inpatient setting (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation